2022
DOI: 10.56093/ijans.v92i3.122268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on egg quality traits of Dahlem Red chicken under intensive system of management in Himachal Pradesh

Abstract: The present study was carried on Dahlem Red chicken breed to assess the effect of age on egg quality traits. Total 250 eggs were collected from birds at different age groups, i.e. 21, 28, 40, 52 and 64 weeks of age for studying the external and internal egg quality parameters. The external characters like egg weight, egg length and egg width were measured. Thereafter, the egg was broken and the internal traits like albumen length, height, width of albumen, yolk height, yolk width, shell thickness were recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 11 publications
1
8
1
Order By: Relevance
“…(2023) [10] also noticed early start of laying in Kadaknath (22±1.12 w) and late in local breed (24.00±2.43 w). Contrary Dinesh et al (2024) [1] reported early (141 days) in native birds and late in Kadaknath (168 days). Thomas et al…”
Section: Age At 1 St Layingmentioning
confidence: 69%
See 4 more Smart Citations
“…(2023) [10] also noticed early start of laying in Kadaknath (22±1.12 w) and late in local breed (24.00±2.43 w). Contrary Dinesh et al (2024) [1] reported early (141 days) in native birds and late in Kadaknath (168 days). Thomas et al…”
Section: Age At 1 St Layingmentioning
confidence: 69%
“…[13] , they have reported 29.43±0.58g weight of day old chick of Kadaknath. In contrary, Dinesh et al (2024) [1] (2020) [6] in his study.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations